Positioning of Resuscitative Endovascular Balloon Occlusion of the Aorta Catheter: A Case of an Elderly Patient with Concomitant Chest and Pelvic Injury after Blunt Trauma - Dongsub Noh; Jeongseok Yun; Ye Rim Chang (Journal of Trauma and Injury)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been increasingly used in recent years as a resuscitative adjunct for trauma patients with life-threatening non-compressible torso hemorrhage. By blocking the aorta temporarily with an inflated balloon, REBOA preserves cerebral and coronary perfusion while diminishing exsanguination below the balloon, thereby providing time for resuscitation and definitive bleeding control. When determining the occlusion zone during the REBOA procedure, factors such tortuosity of the aorta, co-occurring minor chest injuries, and the severity of shock must be considered, as well as the main injury site. This paper describes a case of high Zone I REBOA in an elderly patient with a tortuous aorta who had concomitant injuries of the chest and pelvis.